Implementation of ordering kanban for supplier at company Proreka (M) Sdn Bhd - Lim, Qian Bing (2012)
Lean Production System is a manufacturing management in which time can be shortened for customer order and delivery time; and service parts order can be increased through the elimination of all forms of waste. The main component for “Just-In-Time”, one of the pillars of Lean production System is "Pull System" or Kanban System. Kanban system is a pull system of inventory control that typically uses cards or bins to signal when materials or work-in-process should be moved forward; stock inventory is moved through production stages only when it is needed,and minimizing stock inventories. This is an important revolution in the concept of the Lean Production System. The objective of this research is to simulate Kanban policies for three major materials in warehouse of Proreka (M) Sdn Bhd which is a Malaysia Tier-1 vendor and manufacturer of automotive components. Another objective is to investigate the stock control efficiencies between Material Requirement Planning and Kanban System. The main target of this research is to implement small lot ordering by using Kanban policy to reduce the stock inventories. A simulation model of delivery frequency was developed for the replenishment process of the selected stocks to analyse the delivery frequency from supplier after Kanban implementation. The average stock holding before and after Kanban implementation was analysed to compare the stock control effectiveness between Material Requirement Planning and Kanban System. Interview session and survey by questionnaire were conducted to analyse the performance of Kanban System in point of view of employees. The result obtained indicated that Kanban policy can reduce stock inventories and improve the efficiency in stock control. Other significant improvements with the implementation of Kanban are such as physical condition of the manufacturing environment, production efficiency, and motivation of workers.